Slow-release antibacterial film loaded with clove essential oil based on tapioca starch used for bread preservation - Hui Chang; Ying Zhao; Jie Zhang; Jian Chen; Tao Yang (Food Chemistry: X, 2025)
White pollution is an increasingly serious concern. Consequently, the development of green degradable packaging materials has become a research focus. We incorporated different concentrations of clove essential oil (Ceo) (0 %, 0.5 %, 0.75 %, 1.0 %, and 1.25 %, w/w) into modified tapioca starch to formulate bacteriostatic compound films. The test results indicated that the barrier properties of the Ceo-series composite films surpassed those of the tapioca starch (TS) film. Specifically, the oxygen permeability of the 1.25 % Ceo film was 7.31 g/m2·s, the water vapor permeability decreased to 1.35 g/m2·s, and the oil permeability was reduced to 0.15 g mm m−2 d−1. In addition, the 1.25 % Ceo film exhibited inhibition zones of 4.23 ± 0.28 mm against Staphylococcus aureus and 5.02 ± 0.31 mm against Escherichia coli. In the sustained release test, the Ceo-series composite films demonstrated a uniform and stable release. Furthermore, their degradability reached approximately 70 % by the 20th day. The 1.25 % Ceo film extended the shelf-life of bread to 9 days, exceeding than that of the commercially available polyethylene (PE) plastic wrap. These results highlight that Ceo-series composite films possess outstanding characteristics as active food packaging materials, particularly for noncontact food preservation.